FACTORS INFLUENCING THE PERFORMANCE OF KEY ACCOUNT MANAGERS IN THE INDONESIAN BANKING INDUSTRY - Pratama, Zipora; Sesarea, Sekarsyifa; Kesuma, Meyriana; Fadillah, Fajar; Williams, Andre (International Journal of Application on Economics and Business, 2024)
The banking business stands as a service-oriented enterprise rooted in the principle of trust, where the banking sector heavily relies on service delivery to manage customer trust, thereby ensuring that clients continue to entrust their funds and financial matters to a bank. Within the realm of banking, Key Account Management (KAM) plays a crucial role in maintaining the trust of clients, particularly those classified as Key Accounts (KA). Given the broad spectrum of banking services such as funds deposit and disbursement and considering that bank clients may range from individuals (B2C) to corporations (B2B), banking services must be always delivered at an optimal level. KAM serves as a frontline entity in managing relationships with clients, especially KAs, who are vital for the success of the banking business. This study aims to identify the factors influencing the performance of KAM in the banking sector, for which an in-depth interview was conducted with three Key Account Managers (KA Managers) in the banking industry in Indonesia. The findings reveal both intrinsic and extrinsic factors impacting the performance of KA Managers, with Trust and Solution, as well as Personal attributes, being identified as the primary factors.